Centaurea subsect. Phalolepis in Southern Italy: ongoing speciation or species overestimation? Genetic evidence based on SSRs analyses. Issue 2 (17th February 2019) - Garcia-Jacas, Núria; López-Pujol, Jordi; López-Vinyallonga, Sara; Janaćković, Pedja; Susanna, Alfonso
Abstract : In this paper, we investigated a set of narrow endemics of Centaurea subsect. Phalolepis from the mountains of South Italy (mainly Calabria and Salento), segregated from the widespread species Centaurea deusta, using microsatellite (SSR) markers. The goal was to analyse the genetic makeup (levels and structure) of C. deusta and the segregated species and verify whether genetic clusters were in agreement with current classification of the species. With C. deusta, we also carried out an ecological niche modelling (ENM) analysis to check its potential distribution under present climatic conditions and to project it to the Last Glacial Maximum (LGM). As also found in former studies with subsect. Phalolepis in Greece and Turkey using the same set of SSRs, genetic diversity for the segregated Italian species was higher than expected for narrow endemics with small populations. Genetic clusters, however, were not correlated with the described species and did not support the segregation of the purported narrow endemics from a widely defined C. deusta . The results of the ENM indicate that the Adriatic Sea was a migration corridor for C. deusta at the LGM.